1994
DOI: 10.1103/physrevd.49.4023
|View full text |Cite
|
Sign up to set email alerts
|

Baryon-number fluctuations in a quark-hadron phase transition

Abstract: Isothermal baryon-number fluctuations arising from a first-order quark-hadron phase transition in the early Universe are obtained by including the quark-gluon interactions up to the order gj in the perturbative QCD coupling constant in the quark-gluon plasma (QGP) phase and the finite-size volume corrections for the hadrons in the hadron-resonance gas (HRG) and their effects on the primordial nucleosynthesis (PNS) are analyzed. The ratio of the baryon-number densities in the QGP and HRG phases at the critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Another source of uncertainty in the QGP phase apart from the bag parameter B is the QCD scale parameter . The present calculations have been performed by using the value = 100 MeV [12,16], but a value twice as large is perhaps nearer to what one expects for a standard QCD scale parameter. Since we use a running coupling constant depending on T , µ B and , a variation in may significantly change the results of QGP pressure, and consequently the phase transition.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Another source of uncertainty in the QGP phase apart from the bag parameter B is the QCD scale parameter . The present calculations have been performed by using the value = 100 MeV [12,16], but a value twice as large is perhaps nearer to what one expects for a standard QCD scale parameter. Since we use a running coupling constant depending on T , µ B and , a variation in may significantly change the results of QGP pressure, and consequently the phase transition.…”
Section: Resultsmentioning
confidence: 79%
“…However, there still remain uncertainties in the equation of state (EOS) in both the deconfined and the confined phases. Studies have shown [12] that QCD interactions up to g 3 in the coupling constant are important in the QGP phase, so much so that they not only negate the g 2 contributions, but drive the phase curves away from that of the the zeroth order by an equal amount in the opposite direction.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Here we neglect the logarithmic dependence of α s on µ q . The hadron phase is described by the hadron resonance gas model (HRG) [15][16][17]. Baryons, mesons, and their resonances having masses up to 2 GeV are included.…”
Section: Phase Diagrammentioning
confidence: 99%
“…The baryon number density inhomogeneity arising due to such a quark-hadron phase transition will thus alter the yields of the PNS which is a function of R eq and the neutron to proton (n/p) ratio [10]. Several theoretical attempts have been recently made to determine the values of R eq [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%